An Interview with Nancy Armstrong, Coauthor of The Imaginary Puritan: Literature, Intellectual Labor, and the Origins of Personal Life - Nancy Armstrong (New York City College of Technology, 2019)
Megan Behrent Interviews Nancy Armstrong, the author of The Imaginary Puritan: Literature, Intellectual Labor, and the Origins of Personal Life and “Captivity and Cultural Capital in the English Novel” and answers the question: how should we understand of the role of captivity narratives within the cultural capital of American history?